Social Disasters in Rajasthan: An Analysis: राजस्थान में सामाजिक आपदाएँ: एक विश्लेषण - Chauhan, Poonam (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Since the dawn of civilization, human beings have continuously made necessary arrangements to fulfill the requirements of life, and as a result, humanity has moved towards development. In this development-driven state, numerous obstacles arose before humans, and many challenges stood with open arms. These obstacles or disasters were of two types. One was physical or natural, including earthquakes, floods, volcanoes, cyclones, etc., and the other was the outcome of human nature itself, such as mutual conflicts, quarrels, jealousy, untouchability, differences of opinion, hatred, etc. Against natural disasters, human helplessness has existed for centuries. However, today, with continuously advancing technology, it is possible to predict such disasters in advance. Undoubtedly, science has provided significant relief in the direction of quick solutions to these disasters. On the other hand, there are those disasters that have emerged from within humans while living in society, and centuries have passed while enduring this condition of inequality. During this time, the insightful voices of many great personalities, saints, poets, philosophers, and thinkers echoed with messages of essence and moral values, but humans could not let go of their ego. Prioritizing their own interests or selfish motives, they continued to strike down fellow humans, whether externally or internally. External injuries gradually faded away, and so did the pain, but the internal, mutual attacks and counterattacks made humans venomous. Today, humanity has become so poisonous that even venomous animals consider themselves insignificant in front of human toxicity, and this human poison has started to weigh heavily on voiceless animals as well. Abstract in Hindi Language: सभ्यता के उषा काल से ही मनुष्य ने निरंतर अपने जीवन की आवश्यकताओं की पूर्ति हेतु आवश्यक प्रबंध किए हैं और उसी के फलस्वरूप मानव विकास की ओर उन्मुख हुआ है। इस विकास जनित अवस्था में मनुष्य के समक्ष अनेक बाधाएँ आईं और अनेक चुनौतियाँ मुँह खोले खड़ी रहीं। ये बाधाएँ अथवा आपदाएँ दो प्रकार की थीं। एक तो भौतिक अथवा प्राकृतिक, जिनमें भूकंप, बाढ़, ज्वालामुखी, चक्रवात आदि प्रमुख थीं तथा दूसरी वे जो मानवीय स्वभाव की ही उपज थीं, जैसे - परस्पर लड़ाई-झगड़े, कलह, ईर्ष्या, अस्पृश्यता, मतभेद, घृणा आदि। प्राकृतिक आपदाओं के समक्ष मानवीय विवशता सदियों से बनी हुई है। किंतु आज निरंतर बढ़ती हुई प्रौद्योगिकी के द्वारा इन आपदाओं के पूर्वानुमान प्राप्त किए जा सकते हैं। निःसंदेह विज्ञान के द्वारा इन आपदाओं के त्वरित समाधानों की दिशा में काफी हद तक राहत मिली है। दूसरी ओर वे आपदाएँ हैं, जो समाज में रहते हुए मनुष्य द्वारा स्वयं की उपज हैं और विषमता की इस स्थिति में रहते हुए उसे सदियाँ बीत गईं। इस बीच अनेक महापुरुष, संत, कवि, दार्शनिक, चिंतक आदि की तत्व बोध, मूल्य बोध की वाणियाँ गूंजीं, किंतु मनुष्य अपने अहं का विसर्जन न कर सका और स्वयं के हितों अथवा स्वार्थों को सर्वोपरि रखते हुए दूसरे मनुष्य पर कुठाराघात करता ही रहा, चाहे वह बाह्य हो या आंतरिक। बाहरी रूप से की गई चोट तो धीरे-धीरे मिटती चली गई और दर्द भी मिट गया लेकिन जो आंतरिक परस्पर घात-प्रतिघात होते रहे, इनसे मनुष्य जहरीला हो गया और आज मानव इतना जहरीला हो गया है कि जहरीले जानवर भी स्वयं को मानवीय ज़हर के समक्ष तुच्छ समझने लगे हैं और मानवीय ज़हर उन बेजुबान जानवरों पर भी भारी पड़ने लगा है। Keywords: प्रौद्योगिकी, कुठाराघात, परिवारवाद, संवेदनहीनता, दूरदृष्टि, विघटन, जातिगत, विशुद्ध, समझौतावादी, दकियानूसी, परिपाटी, आक्रान्त, नश्वर।